Developing the professional knowledge of librarians through a webinar series. - Pierce Farrier, Katie; Desjardins, Sandra; Haygood, Laura (Journal of the Medical Library Association, 2025)
Background: The Early Career Librarians Initiative of the South Central Chapter of the Medical Library Association (ECLI) offered a webinar series that addressed topics of interest to new professionals such as networking, goal setting, and salary negotiation. Additionally, the ECLI assessed participant feedback on the series through a program evaluation survey. Case Presentation: ECLI partnered with the Network of the National Library of Medicine (NNLM), Region 3, to offer six webinars over the course of two years. Attendees were asked to complete a survey. Quantitative results were analyzed, and qualitative free-text responses were thematically coded. A total of 567 people attended the webinars, and 154 completed the survey. Four major themes emerged as the most useful aspects of the webinar series: practical tips, encouragement, and real-life experience. Conclusion: Early career librarians often feel overwhelmed and are interested in guidance on career planning and building professional soft skills. This highly attended webinar series and positive evaluation feedback, demonstrates the value of providing accessible online professional development opportunities for early career and transitioning librarians, offering valuable information and support in key areas of need.